If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+v(-3)=6+v
We move all terms to the left:
7+v(-3)-(6+v)=0
We add all the numbers together, and all the variables
v(-3)-(v+6)+7=0
We multiply parentheses
-3v-(v+6)+7=0
We get rid of parentheses
-3v-v-6+7=0
We add all the numbers together, and all the variables
-4v+1=0
We move all terms containing v to the left, all other terms to the right
-4v=-1
v=-1/-4
v=1/4
| 9x-3x+93=9x+51 | | 7^(4x-3)=21 | | 6.2g+4=4.2g+12 | | (3x+16)/2=5 | | 8d+2.8=10 | | 2x-9+x=-39 | | 1x+2=100 | | 5/2+1/2x=5+7/2x | | 132x+2x=3x-2 | | 6-2x=-9x+12 | | 8/x=11/7 | | 2^3x=1.6 | | (2x-41)(x+9)=180 | | 0.76^t=14.75 | | 100=118+2x | | -2x-41=1 | | 56+5x=x-68 | | 10x+14=-2+38 | | -2x+21=1 | | |2x-2|=4 | | y/4+5=9 | | 7p+9=9 | | 11x+5=37 | | 5x+18=17x | | 2/5|5x-10|=4 | | 0.14x+0.1(4000-x)=480 | | -0.07+0.05x=-0.03 | | 7x+5-4x=x-11 | | 4x+5-4x=x-11 | | 5(2x3)-(6)8=13 | | (2/9x)-7=(3/11x) | | 6(2-x)-3(x+7=-45 |